The effect of Cu2+ on arginine kinase from Euphausia superba: A computational simulation integrating unfolding and aggregation studies. Issue 3 (March 2015) - Cheng, Juan-Ge; Si, Yue-Xiu; Lee, Jinhyuk; Zhao, Feng; Yang, Jun-Mo; Qian, Guo-Ying; Yin, Shang-Jun; Park, Yong-Doo
Highlights Arginine kinase from E. superb (ESAK) inactivation mechanisms by Cu2+ ligand binding. Kinetic analysis of Cu2+-induced ESAK aggregation. Several osmolytes roles for preventing ESAK aggregation and recovering activity. Computational molecular dynamics simulation between ESAK and Cu2+.